Dampak Persepsi Harga terhadap Minat Beli Ulang melalui Kepuasan Konsumen pada Luwak White Koffie di Kota Bandung - Amalia, Yunita Nur; Nurtiahiadi, Edi (Journal of Management and Bussines (JOMB), 2024)
This study aims to explore the impact of price perception on repurchase intention through consumer satisfaction at Luwak White Koffie in Bandung City. A quantitative approach was used by collecting primary data from 120 respondents through a questionnaire. Data analysis was carried out by validity testing, reliability testing, classical assumption testing, and linear regression using SPSS version 26 software. The results showed that price perception has a positive effect on consumer satisfaction, which in turn affects repurchase intention. In addition, consumer satisfaction acts as a mediator between price perception and repurchase intention. These findings reveal the importance of paying attention to price perception and consumer satisfaction in increasing repurchase intention. Keywords: Consumer Satisfaction, Repurchase Intention, Price Perception